MEMBANGUN KARAKTER SISWA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN SCRABBLE GAMES - Febri Fajar Pratama (Academy of Education Journal, 2020)
Character education is very important in instilling positive behavior in students. Teachers as educators are expected to be able to internalize the values ​​of character in students through innovative learning in the classroom. One of the method used is to optimize the use of media through game-based learning that are able to change classroom conditions into fun by not eliminating the essence of the learning objectives themselves. The purpose of this study is to describe in depth about the use of learning media as a means of character building through descriptive qualitative approach. The selection of scrabble media is based on the development of learning models applied at SMAN 5 Cimahi through games on the one day one juz program which uses a series of words (verses) to instill the religious character of students. Based on the results of the study concluded that the use of creative learning media can shape student character.